Digital economy sectors are key CO2 transmission centers in the economic system. (25th June 2023) - Wang, Wenhuan; He, Yi; Lei, Yu; Gao, Wenqi; Li, Yineng; Lan, Hanlin; Zhuang, Shiheng; Höök, Mikael
Abstract: The rapid growth of the digital economy has driven economic development, but the massive demand for electricity from digital reforms, coupled with China's coal-based power generation, has created a significant CO2 emission problem. Previous studies have assessed digital economy sectors with an incomplete scope and a lack of carbon emissions assessment at the intermediary-side. To fill these gaps, this study assessed CO2 emissions using input–output modeling of the core industry sector of the digital economy and the industrial digitalization sector at the production, intermediary, and demand sides, and identified key CO2 transmission centers. The results show the following: (1) Digital economy sectors had a high betweenness and were important CO2 transmission centers in the economic system, transmitting more than 4.08 billion tonnes of betweenness-based CO2 emissions; (2) specifically, the industrial digitalization sector transmitted the most CO2 in the economic system, and the digital product manufacturing sector was the core industry sector with the highest betweenness and a strong transmission effect on the CO2 emissions in the supply chain; (3) digital economy sectors had large CO2 emissions on the production, intermediary, and demand sides, and transmitted CO2 more through the demand-side and key transmission centers. These results suggest that digital economy sectors can decarbonize and reduce CO2 emissions by (1) improving material use efficiency in the digital product manufacturing sector, (2) reducing the use of carbon-intensive energy and materials in the digital economy sectors, and (3) establishing CO2 emission disclosure rules, incentives, and penalties. Highlights: The digital product manufacturing sector had high betweenness. Industrial digitalization sector was the largest intermediary-side contributor. Digital economy sectors had large CO2 emissions from three sides. Digital economy sectors influenced upstream CO2 emissions more through demand.